MAPPING FINANCIAL LITERACY: COGNITION AND THE ENVIRONMENT. Issue 2 (14th June 2013) - Clark, Gordon L.
ABSTRACT: Recent research suggests that regions can be characterized according to their (more or less) financial literacy. One implication is that there may be regional ecologies of finance nested within national institutions and global markets. This article begins by situating behaviour in time and space, linking behaviour to the interaction between cognition and the environment. This is followed by a substantive account of the geographical scale of the "environment" working from the global to the local and in return from the local to the global. By implication, maps of financial literacy reflect the skills and expertise of resident populations, affecting how they sort amongst the relevant information to make effective decisions (which have a material effect on their long‐term welfare). Explaining how and why this is the case is one goal of the article. It is also acknowledged that representing the relationship between behaviour and the environment is conceptually and empirically challenging. Reference is made to new findings about the ways in which people "sample" the world around them, suggesting that cognition and the environment are intertwined in ways that may reinforce existing urban and regional inequalities. In conclusion, implications are drawn for the design and implementation of pension and retirement saving policies.